Cost analysis of osteoradionecrosis. Issue 4 (26th January 2017) - Park, L; Lilic, N; Addison, B; Patel, R
Abstract: Objective: Osteoradionecrosis is a significant complication of head and neck cancer treatment, and its most severe form (grade III) necessitates radical surgery. This study aimed to compare the cost of free-flap reconstructive surgery for grade III osteoradionecrosis and similar non-osteoradionecrosis cases in order to assess the cost burden of osteoradionecrosis treatment. Methods: All patients who underwent free-flap reconstructive surgery for osteoradionecrosis between July 2004 and July 2010 at Auckland City Hospital (19 patients) were identified, and relevant data were collected retrospectively. These patients were matched in terms of age and sex with patients who underwent free-flap reconstructive surgery. Results: The treatment cost was 44 per cent higher in osteoradionecrosis patients when compared to non-osteoradionecrosis patients. Conclusion: The significant financial burden on the health system, and the growing evidence for the effectiveness of pentoxifylline, tocopherol and clodronate, should prompt us to explore this alternative treatment further.